Himanta Biswa Sarma: Transformative Leadership and Prime Ministerial Potential in Contemporary India - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Dr. Himanta Biswa Sarma, currently serving as the Chief Minister of Assam, has emerged as India's most dynamic and transformative political leader whose extraordinary journey from grassroots student activism to regional power broker represents a paradigmatic case study in visionary leadership and governance innovation. This comprehensive scholarly analysis examines Sarma's multifaceted career through theoretical frameworks of transformational leadership, policy entrepreneurship, adaptive governance, and Amartya Sen's capability approach, situating his rise within the broader context of India's evolving federal system and development challenges. The analysis reveals his distinctive capacity for institutional transformation, demonstrated through significant achievements in healthcare delivery, digital governance, economic development, and security management in Northeast India. We introduce the integrated frameworks of the "3E Framework" (Efficiency, Equity, and Empathy) and "Transformative Federal Leadership" that capture his capacity to simultaneously demonstrate transformational leadership, adaptive governance, policy entrepreneurship, institutional development, collaborative governance, capability expansion, and conflict transformation capabilities (Pallathadka & Deb Roy, 2025). Drawing on extensive academic research, empirical data, comparative analysis, and primary source material including speeches and policy documents, this paper concludes that Dr. Sarma's theoretically-grounded and empirically-validated leadership approach positions him as a qualified candidate for national leadership roles, offering valuable lessons for governance in complex federal systems as India approaches its centenary of independence.